Amsterdam Koopt kunst : Gemeentelijke Kunstaankopen 87. (Amsterdam : Museum Fodor Amsterdam, 1988)
Bastiaans, Christiaan ; Beelen, Frank ; Bien, Waldo ; Blom, Ansuya ; Breed, Peter ; van den Broeck, Frank ; Brouwn, Stanley ; Buisman, Sjoerd ; Colton, Adam ; Dilworth, Norman ; van Elden, Barten ; Gerrets, Boris ; van Ginneke, Vincent ; Groot, Mieke ; Gudmundsson, Sigurdur ; Homeijer, Kick ; Honing, Willem ; Hooykaas, Madelon ; van der Horst, Loes ; Jacklin, Michael ; Kemps, Niek ; Kleerebezem, Jouke ; Koenings, Christine F. ; Lap, Geert ; Leijenaar, Jorgen ; Lichtveld, Alexander ; Mol, Pieter Laurens ; Mollema, Roel ; Nagelkerke, Anja ; Nielsen, Niels ; Philips, Tejo ; Pink (Hermans, Eugeen) ; Puckey, Tom ; Putte, Loes Van Den ; Reitzema, René ; Ruijgrok, Marc ; Sajet, Philip ; Servaas ; Shabtay, Michal ; Shaw, Jeffrey ; van der Sluis, Ine ; Smit, Robert ; Snijders, Jeroen ; van der Spek, Arjanne ; Stansfield, Elsa ; Strang, Yvonne ; van Tienhoven, Ronald ; Urban, Nikolaus ; de Ven, Rob van ; Veneman, Peer ; Vervoort, Karien ; van der Vleuten, Ton ; Vlugt, Harald ; Vonck, Irene ; Vroegindeweij, Leo ; de Wolf, Lam
biog., tent. per kunstenaar
Amsterdam koopt kunst : Gemeentelijke Kunstaankopen Amsterdam 1987, Museum Fodor Amsterdam, 16.07.1988 - 28.08.1988
Nederlands & Engels
boek
Keywords: Amsterdam